ROLE OF INTERDISCIPLINAR INTEGRA-TION IN MOTIVATION OF BIOPHYSICS AND MEDICAL PHYSICS’s STUDY - Ischeikina, Yu.A. (World of Medicine and Biology, 2012)
Organization of educational process of department of medical informatics and medical and biological physics, sent to the orientation and motivation the students of study of discipline, which will be needed for practical activity in the future with the purpose of diagnostics of illnesses and their successful treatment, and also planning of effective measures in relation to their prophylaxis.
Keywords: interdisciplinar integration; educational process; biophysics; medical physics; medical informatics